Empowering Grated Coconut MSMEs in Semarang: A Social Marketing Approach to Strengthen Brand Image - Ahmad Reza; Diana Aqmala; Erin Kristina (BUSMI : Journal of Business and Management Innovations, 2025)
Social marketing is one way a company can improve its brand image and be better known. Social marketing activities can be based on activities such as caring for the environment and minimal waste generated from the business activities of an MSME or company. The purpose of this study is to identify more deeply the basis of social marketing, whether it can improve the business's brand image or not, and with social marketing, the business can also provide benefits that have a good impact on the social environment of the community. This research was carried out using qualitative methods by conducting in-depth interviews with grated coconut business owners, consumers, and residents around the running grated coconut business environment, which in this study were taken from several Grated Coconut SMEs in Semarang City. The results of this study are in the form of a new social marketing model as a basis for initiating MSME brand image enhancement or an effort to increase MSME awareness of the importance of running a business by considering environmental conditions. The contribution of this research is that the model will make it easier for Grated Coconut MSMEs to implement social marketing. It can also be the beginning of the awareness process of MSME business actors on the importance of protecting the environment when running business operations.